2014
DOI: 10.2298/apt1445079p
|View full text |Cite
|
Sign up to set email alerts
|

The content of buckwheat flour in wheat bread

Abstract: Seven samples of bread were prepared in a special way. Samples were made of a mixture of wheat and buckwheat flour in defined proportions. Carbohydrates from crumbs of bread were derivatized with BSTFA and analyzed by GC-MS. Multivariate analysis was applied. The purpose of this study was not the identification and quantification of carbohydrate composition. The results demonstrated a clear relation between the carbohydrate composition of the bread samples and the type of flour used for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…The lowest L * value (60.71) was obtained for the sample with the large particle size, suggesting a dark bread. Our results fall in line with those obtained by Psodorov et al [ 60 ] who observed an increase in redness and yellowness intensity, and a decrease in bread lightness with an increase in buckwheat flour dose. On the other hand, the amino acids present in optimal composite flours participate in the formation of melanoidins that color the crust of the bread.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The lowest L * value (60.71) was obtained for the sample with the large particle size, suggesting a dark bread. Our results fall in line with those obtained by Psodorov et al [ 60 ] who observed an increase in redness and yellowness intensity, and a decrease in bread lightness with an increase in buckwheat flour dose. On the other hand, the amino acids present in optimal composite flours participate in the formation of melanoidins that color the crust of the bread.…”
Section: Discussionsupporting
confidence: 94%
“…This phenomenon may be related to the lower amount of gluten replaced, which will generate spatial structure modification of gliadin and glutenin molecular chains, with strong disulfide bonds that lead to inter- or intramolecular interactions of disulfide, ionic, or hydrogen bonds [ 59 ]. Some authors affirmed that the replacement of wheat flour with a high content of buckwheat flour (up to 20%) determined a decrease in loaves’ volume, probably due to the change in the gluten network and the fiber content which are able to retain fermentation gases [ 56 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary results obtained in this study are in accordance with the results, which indicate that other small molecules (suitable for the analysis by GC-MS system, such as simple sugars) can be used for the determination of buckwheat flour in bread [14], with the application of multivariate analysis of GC-MS data, without performing quantitative determinations.…”
Section: Resultssupporting
confidence: 88%
“…In previous studies [12,13] it has been proven that it is possible to unambiguously distinguish buckwheat flour from wheat flour, based on GC-MS and multivariate analysis of characteristic ions of (1) simple sugars in alcoholic extracts of flour samples, and (2) fatty acid methyl esters and non-saponifiable components in fatsoluble (hexane) extracts of flour samples. Previous research has also shown that it is possible to determine the content of buckwheat flour in crusts and crumbs of bread samples with addition of buckwheat flour, based on the content of simple sugars and methyl esters of dominant fatty acids [14,15].…”
Section: Introductionmentioning
confidence: 99%